2001
DOI: 10.1075/eurosla.1.15cel
|View full text |Cite
|
Sign up to set email alerts
|

Short and mid-term effects of an earlier start

Abstract: Most studies concerning the issue of age have focused on the language outcomes of subjects who started acquiring a second language during childhood, or later on during adolescence or adulthood in naturalistic contexts. However, relatively few studies have been concerned with school contexts where a foreign language is a compulsory subject in the early stages of the curriculum. The aim of the present study is to address the question of the effects of starting age (8 versus 11) on the acquisition of English as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…These findings confirm the poor results obtained by young students in educational settings in studies conducted in other contexts (Burstall 1975;Cenoz 2002a;Ekstrand 1976;Muñ oz 2000Muñ oz , 2003Celaya et al 2001). Cenoz (2003b) also found that when the levels of proficiency of learners who were in the same course but started learning English at di¤erent ages are compared, the number of hours of instruction does not necessarily imply a higher level of proficiency in English.…”
Section: The E¤ect Of Early Instruction In English On the Developmentsupporting
confidence: 71%
“…These findings confirm the poor results obtained by young students in educational settings in studies conducted in other contexts (Burstall 1975;Cenoz 2002a;Ekstrand 1976;Muñ oz 2000Muñ oz , 2003Celaya et al 2001). Cenoz (2003b) also found that when the levels of proficiency of learners who were in the same course but started learning English at di¤erent ages are compared, the number of hours of instruction does not necessarily imply a higher level of proficiency in English.…”
Section: The E¤ect Of Early Instruction In English On the Developmentsupporting
confidence: 71%
“…An exception to this trend is Torras et al (2006) large-scale study of a group of 495 EFL learners in Barcelona (Spain) at the primary and secondary school level. On the basis of Wolfe-Quintero, Inagaki and Kim's (1998) discussion of writing measurements and of Celaya, Torras and Pérez-Vidal's (2001) previous work, they measure written development, with a product-oriented perspective. They purport to take a fresh "wider perspective" in the analysis of written competence by focusing on "interlanguage development" (Torras et al 2006: 156).…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical framing in research may position written proficiency as composed of a large number of specific subsystems that develop differently and independently, but we are not always sure of the implications for practice (e.g., Celaya, Torras, & Perez‐Vidal, ). Also, while there are many studies on error correction, it is still an open question whether and how teachers' responses can be linked to improvement in students' writing (Casanave, ).…”
Section: Resultsmentioning
confidence: 99%